Lived Experience of Treatment for Avoidant Personality Disorder: Searching for Courage to Be - Sørensen, Kristine Dahl; Wilberg, Theresa; Berthelsen, Eivind; Råbu, Marit (Frontiers in Psychology, 2019)
Objective: To inquire into the subjective experience of treatment by persons diagnosed with avoidant personality disorder. Methods: Persons with avoidant personality disorder (N = 15) were interviewed twice, using semi-structured in-depth interviews, analyzed by and the responses subject to interpretative-phenomenological analysis. Persons with firsthand experience of avoidant personality disorder were included in the research process. Results: The superordinate theme emerging from the interviews, “searching for courage to be” encompassed three main themes: “seeking trust, strength, and freedom,” “being managed,” and “discovering the possibility for change and development.” The main theme, “being managed,” included the subthemes: “getting a diagnosis,” “receiving medication,” and “attending therapy.” Conclusion: Although this may not be specific to avoidant personality disorder, Ttheese findings highlight the importance, importance of being met intersubjectively as a person with intentionality and agency, even when one does not feel like one.as an agentive intentional being, even when one does not feel like one, of being met intersubjectively by a therapist. The importance of establishing an emotional bond and emergent trust for open therapeutic communication, collaboration, learning, and becoming able to build courage to begin to approach that which one fears, is emphasized.